Staged history: Concept of theatricality in the modern utopia (England, England by Julian Barnes) - Filimonova, Alexandra P. (Вестник Томского государственного университета. Филология)
The work explores the concept of theatre and the role of theatrical conventions in Julian Barnes’s utopian novel England, England. This article discusses theatricality as the principal artistic strategy of the novel, heavily influencing its formal and thematic structure. It outlines the main characteristics of the theatrical chronotope, and considers the similarities between theatricality and the conventions of the utopian novel per se. It examines closely the way Barnes exploits the various semantic implications of the chronotope in his critique of contemporary society. Methodologically the article is based on the findings of theatre semiotics and employs them as its theoretical framework (Alter, Fischer-Lichte, Pavis), while also considering sociological (Debord), anthropological (Milton Singer, Geertz Clifford), and psychological (Erving Goffman) approaches to the phenomena of theatre. Tightly intertwined with actual cultural and social strategies, theatre has always been an essential integrative part of social life. The author uses theatricality to take a reflective attitude towards the contemporary culture, to examine and display the political and social strategies which are considered as immanently theatrical. Under the theory of theatrical semiotics, the decisive aspects of theatre as an aesthetic system are theatrical space and time. The main characteristics of the theater are conceptualized primarily in the theatrical chronotope. On this ground, it can be argued that the significant structural element through which theatricality is incorporated in novelistic discourse is that of the artistic chronotope. The specific enclosure of the theatre universe manifested within the typical utopian locus serves to arrange it as the space of utopian social experiment perfecting the latent tendencies of the culture and exposing them to critical observation. Theatrical “a-temporality” correlates with utopian “a-historicity” and unfolds the rupture with the historical continuum which gives free rein to its purposeful reconstructions. Theatrical images are subjected to regrouping in eclectic totality and re-combinations of disrupted elements of the historical continuum. The cyclicity of the performances representing historical and mythical figures and the re-enacting events essential for national identity involves the spectators in pseudo-communication. It actually deprives them of experiencing real time and space, replacing it with the comfortable pseudoexperience of consuming surrogate images. Thus, the main characteristics of theatrical chronotope are employed to develop the novel’s essential concerns with such issues as reconstruction of individual and national identity and their subjection to distorting speculations. Theatricality reveals the nature of a forward-looking industrial society as a commercial spectacle turning national culture and history into a manipulated commodity.